Tracking pythons : the quest to catch an invasive predator and save an ecosystem - Messner, Kate (Millbrook Press, 2020)
Explores attempts to track and capture pythons, an invasive species, in Florida in order to save the state's ecosystem. Discusses the snake's physical traits, behaviors, habitat, life cycle, and diet. Includes a timeline, a list of invasive species, sidebars, color photographs, a glossary, and further resources.